The genome sequence of fat-hen, Chenopodium album L. [version 2; peer review: 2 approved, 1 approved with reservations] - Sahr Mian; Maarten J. M. Christenhusz (Wellcome Open Research, 2024)
We present a genome assembly from an individual Chenopodium album (fat-hen; Streptophyta; Magnoliopsida; Caryophyllales; Chenopodiaceae). The genome sequence has a total length of 1,593.80 megabases. Most of the assembly (99.61%) is scaffolded into 27 chromosomal pseudomolecules suggesting the individual is an allohexaploid (2n = 6x = 54). The mitochondrial and plastid genome assemblies have lengths of 312.95 kilobases and 152.06 kilobases, respectively. Gene annotation of this assembly on Ensembl identified 50,077 protein-coding genes.